IL‐2Rα is a potential biomarker for heart failure diagnosis of patients with end‐stage renal disease and haemodialysis - Bingya Lv; Zhe Wang; Ya Suo; Shuai Shao; Meng Yuan; Yue Zhang; Lihua Wang; Guangping Li; Qiankun Bao (ESC Heart Failure)
Abstract Aims Heart failure (HF) is a leading cause of mortality in patients with end‐stage renal disease (ESRD) undergoing haemodialysis. Identifying novel predictors of HF is essential for improving diagnostic precision and enhancing patient outcomes. Methods This study included 68 participants from the Haemodialysis Centre at the Second Hospital of Tianjin Medical University. Clinical characteristics and echocardiographic data were collected and analysed. We measured the plasma of 44 cytokines to investigate their correlation with cardiac function and their potential as HF biomarkers. Results In the HF with reduced ejection fraction (HFrEF) group, the levels of several cytokines, including stem cell growth factor‐β (SCGF‐β), C–X–C motif chemokine 10 (CXCL10), interleukin‐1α (IL‐1α), interleukin‐6 (IL‐6), interleukin‐8 (IL‐8), interleukin‐16 (IL‐16), interleukin‐1 receptor antagonist protein (IL‐1Ra), interferon‐γ (IFN‐γ), tumour necrosis factor‐α (TNF‐α), leukaemia inhibitory factor (LIF), C–C motif chemokine 3 (CCL3), interleukin‐10 (IL‐10), interleukin‐2 receptor subunit alpha (IL‐2Rα), tumour necrosis factor ligand superfamily member 10 (TNFSF10), macrophage colony‐stimulating factor (M‐CSF), granulocyte colony‐stimulating factor (G‐CSF) and stem cell factor (SCF), were significantly increased, while C–C motif chemokine 11 (CCL11)/eotaxin levels were decreased compared with those in the control group (P < 0.05). Receiver operating characteristic (ROC) curve analysis highlighted TNF‐α [area under the ROC curve (AUC) = 0.85, odds ratio (OR) = 1.080, 95% confidence interval (CI): 1.033–1.128, P = 0.001], IFN‐γ (AUC = 0.84, OR = 1.836, 95% CI: 1.289–2.615, P = 0.003) and IL‐2Rα (AUC = 0.82, OR = 1.022, 95% CI: 1.009–1.035, P = 0.001) as excellent predictors for HFrEF in haemodialysis patients with ESRD, and they outperformed soluble suppression of tumourigenicity‐2 (sST2) but slightly underperformed N‐terminal pro‐brain natriuretic peptide (NT‐proBNP). IL‐2Rα (AUC = 0.77, OR = 1.018, 95% CI: 1.007–1.030, P = 0.001) demonstrated superior diagnostic capabilities when distinguishing patients with HF with left ventricular ejection fraction (LVEF) <50% from controls. IL‐2Rα emerged as a robust biomarker for left ventricular HF, while TNF‐α (AUC = 0.89, OR = 1.140, 95% CI: 1.039–1.250, P = 0.005) showed promise in assessing HF severity in patients with ESRD. IL‐2Rα (AUC = 0.80, OR = 1.017, 95% CI: 1.007–1.027, P = 0.001) also significantly predicted right ventricular systolic dysfunction. During a median follow‐up of 14 months, 10 patients (14.7%) experienced all‐cause mortality. Multivariate Cox regression analysis confirmed that plasma IL‐2Rα was an independent predictor of all‐cause death [hazard ratio (HR): 1.010, 95% CI: 1.001–1.020, P = 0.039] after adjusting for other variables. Conclusions This study underscores the potential of IL‐2Rα as a valuable biomarker for HF diagnosis and management in haemodialysis patients with ESRD and contributes to our understanding of this high‐risk population.